Characterization of mouse flavin-containing monooxygenase transcript levels in lung and liver, and activity of expressed isoforms - Siddens, Lisbeth K. (2007)
The significance of active vs. inactive flavin-containing monooxygenase 2 (FMO2) for human drug and xenobiotic metabolism and sensitivity is unknown, but the underlying ethnic polymorphism is well documented. We used quantitative real-time PCR to measure message levels of Fmo1, Fmo2, Fmo3 and Fmo5 in lung and liver from eight strains of eight week old female mice to determine if a strain could be identified that predominately expressed Fmo2 in lung, recapitulating the human FMO expression profile and being the ideal strain for Fmo2 knockout studies. We also characterized enzyme activity of baculovirus expressed mouse Fmo1, Fmo2 and Fmo3 to identify a substrate or incubation conditions capable of discriminating Fmo2 from Fmo mixtures. Fmo transcript expression patterns were similar for all strains. In lung, 59% of total FMO message was Fmo2, but Fmo1 levels were also high, averaging 34%, whereas Fmo3 and Fmo5 levels were 2 and 5%, respectively. In liver, Fmo1, Fmo2, Fmo3 and Fmo5 contributed 16, 1, 7 and 76% respectively, of detected message. Peak activity varied by isoform and was pH- and substrate-dependent. Fmo3 oxidation of methyl p-tolyl sulfide was negligible at pH 9.5, but Fmo3 oxidation of methimazole was comparable to Fmo1 and Fmo2. Heating microsomes at 50 °C for 10 min eliminated most Fmo1 and Fmo3 activity, while 94% of Fmo2 activity remained. Measurement of activity in heated and unheated lung and liver microsomes verified relative transcript abundance. Our results show that dual Fmo1/2 knockouts will be required to model the human lung FMO profile.